Sistem Informasi Pelayanan Pelanggan Baru Menggunakan PHP dan MySQL (Studi Kasus : PDAM Barabai) - Rafii, Muhammad; Sofyar, Sofyar; Risdayati, Sunni (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
The development of information technology, particularly information systems, is increasingly optimized by users to facilitate the operations of a company. PDAM Tirta Dharma, as a state-owned company engaged in public services, specifically in the provision of drinking water, recognizes the need to utilize an information system to streamline its operations in order to enhance the quality of service to the community. The implementation of a new water connection system is one of the strategies employed by PDAM Tirta Dharma to simplify the process for both individual consumers and installations or companies. As an institution, PDAM Tirta Dharma requires a computerized system to process data and handle new customer services. The ease of registration for potential customers is a crucial aspect that needs attention. Therefore, the development of a new customer information system is essential for PDAM Tirta Dharma. This system is constructed using the PHP programming language and MySQL, which are popular programming languages. It is supported by the Bootstrap framework based on HTML5 and CSS. The existing manual system faced various challenges and issues. This research is expected to assist in streamlining the new customer registration process.